Feminising hormone therapy reduces testicular ACE‐2 receptor expression: Implications for treatment or prevention of COVID‐19 infection in men. (13th September 2021) - Masterson, John M.; Bui, Chau; Zhang, Yi; Yuan, Xiaopen; Huynh, Carissa; Jawanda, Harneet; Hasan, Wohaib; Tourtellotte, Warren; Luthringer, Daniel; Garcia, Maurice M.
Abstract: It has been proposed that men hospitalised with COVID‐19 be treated with oestrogen or progesterone to improve COVID‐19 outcomes. Transgender women (male‐to‐female) are routinely treated with oestrogen or oestrogen +progesterone for feminisation which provides a model for the effect of feminising hormones on testicular tissue. Our goal was to analyse differences in ACE‐2 expression in testicles of trans‐women taking oestrogen or oestrogen +progesterone. Orchiectomy specimens were collected from trans‐women undergoing gender‐affirming surgery, who were taking oestrogen or oestrogen+progesterone preoperatively. For controls, we used benign orchiectomy specimens from cis‐gender men. All specimens were stained with H&E, Trichrome (fibrosis), insulin‐like 3 antibody (Leydig cell) and ACE‐2 IHC. Cells per high‐powered field were counted by cell type (Leydig, Sertoli and Germ). Stain intensity was rated on a 0–2 scale. On immunohistochemistry staining for Leydig cells and ACE‐2 staining, the oestrogen+progesterone cohort had fewer Leydig cells compared with controls. The oestrogen+progesterone cohort also had greater degree of tissue fibrosis compared with controls and the oestrogen cohort. This work supports the hopeful possibility that a short course of progesterone (or oestrogen+progesterone) could downregulate ACE‐2 to protect men from COVID‐19 infection.